Differentiated Learning Models in the Context of Islamic Education: A Critical Literature Review - Wawan Saputra (Journal of Educational Studies, 2025)
This study aims to analyze the concepts, implementation, challenges, and relevance of differentiated learning models in the context of Islamic Religious Education (PAI) through a critical literature review approach. This research is motivated by the demands for educational transformation in the era of the Merdeka Curriculum and 21st-century education, which emphasize student-centered learning. The research method employed is a critical literature review by examining various scholarly sources, including journals, books, and academic documents relevant to differentiated learning and Islamic education. The data were analyzed through processes of data reduction, categorization, interpretation, and critical synthesis to identify patterns, concepts, and research gaps. The findings reveal that differentiated learning has strong relevance to the development of PAI instruction, as it is capable of accommodating the diverse characteristics, needs, and potentials of students. The implementation of differentiated learning in PAI is carried out through the differentiation of content, processes, products, and learning environments, which positively impact students’ engagement, motivation, and learning experiences. Furthermore, differentiated learning is also aligned with the principles of Islamic education, which value human nature (fitrah) and human potential holistically. However, its implementation still faces various challenges, such as limited teacher competence, inadequate diagnostic assessment, conventional learning cultures, and insufficient learning facilities. This study contributes conceptually by positioning differentiated learning not merely as a pedagogical strategy, but also as a humanistic approach to transforming Islamic Religious Education learning in the modern era.